Tourism preferences of seniors and their impact on healthy ageing. Issue 4 (2nd October 2021) - Patterson, Ian; Balderas-Cejudo, Adela; Pegg, Shane
ABSTRACT: Our world is growing older at its fastest rate in history. This explosion in the ageing population has become increasingly attractive to the global tourism industry. Little attention has been paid to the impact of travel experiences on the health of senior tourists. This study explores the travel preferences of seniors and the health benefits that tourism can play. This study used a qualitative methodology interviewing 20 senior adults living in the UK aged between 55 and 80 years. The results identified two major themes relating to preferences in regard to time and travelling companions, and travelling for health purposes. Travel was found to have a positive influence on seniors and helped to contribute to a healthy lifestyle.